Extensive Thrombosis of the Inferior Vena Cava and Left Renal Vein in a Neonate - Moez Kdous; Oussema Khlifi; Marwene Brahem; Mohamed Khrouf; Sarah Amari; Monia Ferchiou; Fethi Zhioua (Hindawi Limited, 2015)
Antenatal renal vein thrombosis is a rarely described diagnostic finding, with variable consequences on kidney function. We present the case of an affected fetus, born at 35-week gestation, with intrauterine oligohydramnios and two small kidneys. A renal ultrasound carried out after birth confirmed the presence of prenatal abnormalities. Renal vein thrombosis was not diagnosed at the time. The baby died 20 days later of kidney failure, metabolic acidosis, and polypnea with severe hypotrophy. Autopsy revealed atrophied kidneys and adrenal glands. The vena cava had thrombosis occupying most of its length. The right renal vein was normal, while the left renal vein was threadlike and not permeable. Histologically, there was necrosis of the left adrenal gland with asymmetrical bilateral renal impairment and signs of ischemic and hemorrhagic lesions. A review of thrombophilia was carried out and a heterozygous mutation in Factor V was found in both the mother and the child.